THE EMPLEMENTATION OF ENTERPRISE ARCHITECTURE PLANNING (EAP) MODEL FOR INFORMATION SYSTEM DEVELOPMENT AT HUMAN RESOURCE DEPARTMENT - Yunus, Halimah (Prosiding International conference on Information Technology and Business (ICITB), 2015)
Investment failure in the field of information technologyto improve the company performance mostly happensbecause the planning is maximal. One method toovercome this investment failure is by developing aplanning process of information system development,consisting of data architecture, application architecture,and architecture.The method used in constructing the enterprisearchitecture model is Enterprise Architecture Planning(EAP). EAP explains about data, application, andtechnology which will be required to support the businessprocess at the Human Resource (SDM) bureau where itwill be able to produce a blueprint for data architecture,application and technology as well as the planimplementation aimed at providing the needs withsustainable detail level in applying the idea of the systembuilt.In architecture EAP explains about data, application andtechnology to be used to support the business process atHuman Resource bureau where it will produce a blueprintfor data architecture, application and technology as wellas implementation plans aimed at providing the needswith the sustainable detail level in applying the idea tobuild the system.The construction of the enterprise architecture model ofSDM bureau at IBI Darmajaya is limited on employeeaffairs and not focused on the application or technicaldesign.KEY WORDS : EAP, Enterprise Architecture